Research on Influence of Water-Cement Ratio on Reinforcement Effect for Permeation Grouting in Sand Layer - Zhipeng Li; Lianzhen Zhang; Yuntian Chu; Qingsong Zhang (Advances in Materials Science and Engineering)
In order to study permeation grouting reinforcement effect in the sand layer, a set of grouting test device is developed, which consists of a power device, a pressure-bearing slurry tank, and several test frames. Compressive strength, deformation modulus, and permeability coefficient are selected to be the evaluation index of grouting reinforcement effect. Grouting reinforcement effect under different water-cement ratio of cement slurry and curing time were measured. Eventually, under laboratory conditions, fitting formulas have been obtained which describe the quantitative relationship between reinforcement effect of permeation grouting and water-cement ratio and curing time. Results show that water-cement ratio of slurry has obvious effect on grouting reinforcement effect. Mechanical performance and impermeability of the grouted body are negative-correlated with water-cement ratio. There are two different destruction patterns for the grouted body in uniaxial compression process: global destruction pattern at low water-cement ratio and local destruction pattern at high water-cement ratio. If cement slurry at high water-cement ratio is permeated into the sand layer, water bleeding phenomena will appear and lead to inhomogeneous performance of the grouted body, with lower performance in the upper part and higher performance in the lower part of the grouted body.